(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Blood pressure depends on cardiac output and systemic vascular resistance. Key regulators: Sympathetic nervous system, RAAS (Renin–Angiotensin–Aldosterone System), endothelial function, and renal sodium handling. Dysregulation leads to persistent elevation of blood pressure. Blood pressure fluctuates throughout the day and night. The pattern of blood pressure values obtained during the sleep-wake cycle from characteristic circadian rhythm.The treatment of hypertension not only includes the usual clinical goal of reducing mean blood pressure levels, but also the normalization of the entire blood pressure circadian pattern.ECG, AV nodal function have been shown to exhibit circadian variations.Chronotherapeutics treatment strategy that involves the delivery of medications so they are synchronized in time to biological need that varies according to the chronobiology of the targeted tissue.Evidences suggest that basic electrophysiological parameters have circadian variations.In the present study, pulsatile release formulations of Cilnidipine were successfully designed and optimized to achieve chronotherapeutic drug delivery. The core tablets were prepared by direct compression using Sodium Starch Glycolate as a superdisintegrant, Microcrystalline Cellulose as a diluent, and Magnesium Stearate as a lubricant and glidant. The optimized core formulation was selected based on its drug release performance.Comprehensive Preformulation studies, including evaluation of organoleptic properties, angle of repose, bulk density, tapped density, compressibility index, Hausner’s ratio, melting point, and solubility, confirmed that all parameters complied with pharmacopeial specifications. Characterization of the drug was carried out using UV and IR spectroscopy. The IR spectral analysis confirmed the absence of drug–excipient interactions, while UV analysis revealed characteristic absorption maxima (λmax) at 202 nm and 240 nm.